Hyperthermic intraperitoneal chemotherapy in interval debulking surgery for advanced epithelial ovarian cancer: A single‐center, real‐life experience. Issue 24 (15th September 2020) - Ghirardi, Valentina; Ronsini, Carlo; Trozzi, Rita; Di Ilio, Chiara; Di Giorgio, Andrea; Cianci, Stefano; Draisci, Gaetano; Scambia, Giovanni; Fagotti, Anna
Abstract : Background: An improvement in survival without increasing perioperative morbidity in patients with advanced epithelial ovarian cancer treated with hyperthermic intraperitoneal chemotherapy (HIPEC) after interval debulking surgery (IDS) has been recently demonstrated in a randomized controlled trial. This study was aimed at assessing the feasibility and perioperative outcomes of the use of HIPEC after IDS at a referral cancer center. Methods: Over the study period, 149 IDSs were performed. Patients who had at least International Federation of Gynecology and Obstetrics stage III disease, with <2.5 mm of residual disease (RD) at the end of surgery and were not participating in clinical trials received HIPEC. Moreover, specific exclusion criteria were considered. These patients were compared with 51 patients with similar clinical characteristics at the same institution and within the same timeframe who did not receive HIPEC. Results: No differences in patient or disease characteristics with the exception of the type of neoadjuvant chemotherapy ( P = .002) were found between the 2 groups. As for surgical characteristics, significant differences were found in RD after IDS ( P = .007) and in the duration of surgery ( P < .001), whereas the bowel resection and diversion rates ( P = .583 and P = .213, respectively) and the postoperative intensive care unit and hospital stays ( P = .567 and P = .727, respectively) were comparable. The times to start adjuvant chemotherapy were also similar ( P = .998). Equally, the rates of any grade of both intraoperative complications ( P = .189) and early postoperative complications ( P = .238) were superimposable. Conclusions: In the authors' experience, the addition of HIPEC to IDS is feasible in 35% for the population. This value might increase with changes in the inclusion/exclusion criteria. HIPEC does not increase perioperative complications and does not affect a patient's recovery or time to start adjuvant chemotherapy. HIPEC should be offered to select patients listed for IDS. Abstract : Hyperthermic intraperitoneal chemotherapy does not increase perioperative complications and does not affect a patient's recovery or time to start adjuvant chemotherapy. Hyperthermic intraperitoneal chemotherapy should be offered to select patients listed for interval debulking surgery.